Rough Sets and Intelligent Systems Paradigms Second International Conference, RSEISP 2014, Granada and Madrid, Spain, July 9-13, 2014. Proceedings - Kryszkiewicz, Marzena; Cornelis, Chris; Ciucci, Davide; Medina-Moreno, Jesús; Motoda, Hiroshi; Ras, Zbigniew (Lecture Notes in Artificial Intelligence,, 2014)
This book constitutes the refereed proceedings of the 23rd Australasian Joint Conference on Rough Sets and Intelligent Systems Paradigms, RSEISP 2014, held in Granada and Madrid, Spain, in July 2014. RSEISP 2014 was held along with the 9th International Conference on Rough Sets and Current Trends in Computing, RSCTC 2014, as a major part of the 2014 Joint Rough Set Symposium, JRS 2014. JRS 2014 received 40 revised full papers and 37 revised short papers which were carefully reviewed and selected from 120 submissions and presented in two volumes. This volume contains the papers accepted for the conference RSEISP 2014, as well as the three invited papers presented at the conference. The papers are organized in topical sections on plenary lecture and tutorial papers; foundations of rough set theory; granular computing and covering-based rough sets; applications of rough sets; induction of decision rules - theory and practice; knowledge discovery; spatial data analysis and spatial databases; information extraction from images.